Effect of V2O5 Dopant on the Electrical Conductivity of RuO2 Thick Film Resistors - M. S. Setty; R. F. Shinde (Active and Passive Electronic Components)
Thick film glaze resistors have been prepared using V2O5 doped RuO2 conducting phase. Different amounts of V2O5 were incorporated into RuO2lattice by solid state reaction. Sheet resistivity decreased from 235 to 10 kΩ/Sq, with the increase in the dopant concentration from 2 to 6% wt. The conductivity, ‘σ’, was found to fit in the equation σ= KS(l-S), where S is the probability that a given cationic site will contain an extra charge carrier and K = 10-3 mho-sq.